PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF ISLAMI UNTUK ANAK USIA DINI DALAM MENANAMKAN NILAI-NILAI KEAGAMAAN DI TAMAN KANAK-KANAK NURUL ISTIQOMAH DESA MUARO PANCO KABUPATEN MERANGIN - Faiza Putri; Ridwan; Sapriya Utami (STKIP Subang, 2026)
This study aims to examine the use of Islamic interactive learning media in instilling religious values in early childhood at Nurul Istiqomah Kindergarten, Muaro Panco Village, Merangin Regency. Early childhood education is a crucial phase in character development, particularly in embedding religious values as the foundation of children’s moral behavior. However, religious learning in many institutions is often still delivered through conventional methods that are less engaging. Therefore, learning innovation through Islamic interactive media is needed to create enjoyable and meaningful religious learning experiences. This research employed a qualitative approach with a descriptive research design. The research subjects consisted of teachers and early childhood learners at Nurul Istiqomah Kindergarten. Data were collected through observation, interviews, and documentation. Data analysis was conducted using data reduction, data display, and conclusion drawing, while data validity was ensured through triangulation. The findings indicate that the use of Islamic interactive learning media, such as Islamic animated videos, religious children’s songs, and educational games, increases children’s learning interest and facilitates their understanding of religious concepts like daily prayers and manners in a more concrete way. The obstacles encountered include limited supporting facilities and teachers’ constraints in independently developing interactive media. Overall, Islamic interactive learning media are effective in instilling religious values in early childhood learners at Nurul Istiqomah Kindergarten.